A numerical study on hydrodynamic and heat transfer characteristics of gas–liquid Taylor flow in horizontal mini tubes. (8th October 2021) - Lei, Li; Cheng, Cheng; Huang, Nanyan; Xin, Gongming; Zhang, Jingzhi; Wang, Xinyu
Abstract: The flow and heat transfer characteristics of gas-liquid Taylor flows in a horizontal tube with 3.12 mm inner diameter were studied numerically with the volume of fluid method. The bubbles are patched using the user defined functions based on the experimental volumes and formation frequencies. Numerical results agree well with the experimental results and empirical correlations. The results indicate that the gravity plays an important role in the Taylor flow in mini tubes. The bubble shape is asymmetric and the normalized film thickness is larger at the tube bottom. The wall shear stress in the liquid region remains approximately unchanged, while there is a sharp increase near the tail and nose of bubbles. The pressure distribution is divided into four parts, and the presence of air increases the pressure gradient. The internal recirculation in the liquid slug can enhances the heat transfer coefficients.